Responses of Tomato Crop and Water Productivity to Deficit Irrigation Strategies and Salinity Stress in Greenhouse - Akram K. Alshami; Ahmed El-Shafei; Abdulrasoul M. Al-Omran; Abdulaziz G. Alghamdi; Ibrahim Louki; Arafat Alkhasha (Agronomy, 2023)
Saudi Arabia faces water scarcity and inadequate sustainable sources, particularly in agriculture, necessitating efficient irrigation water management to improve productivity amidst rising demand. The study investigated the impact of irrigation levels and water salinity on tomato plants in greenhouses, covering four irrigation levels (100%, 80%, 60%, and 40% of ETc) and three water sources (FW (0.9 dS·m−1), SW (3.6 dS·m−1) and MW (2.25 dS·m−1)). Salinity impacts crop yield, physiological responses, and fruit quality. The photosynthesis, stomatal conductance, transpiration, and chlorophyll content decrease with MW and SW, negatively affecting morphological characteristics. For MW, it was recommended to apply 60% deficit irrigation with a yield of 98 kg·ha−1, and water productivity (WP) improved to 21.93 kg·m−3 compared to 13.65 kg·m−3 at full irrigation (FI). In SW, 80% irrigation was suggested, as there was no significant difference in yield compared to FI. For FW, 60% deficit irrigation produced the best water conservation (104.58 kg·ha−1 yield and 23.19 kg·m−3 WP), while FI produced the highest yield per unit area (123.48 kg·ha−1 yield and 16.51 kg·m−3 WP). Nonetheless, greater water and salinity stress was associated with increased fruit quality measures such as total acidity, vitamin C, and soluble solids. The results show that implementing deficit irrigation with salinity strategies in greenhouse tomatoes could improve crop adaptability, yield, and water productivity in the face of water scarcity and salinity variability.